Dental Transplantation - P. Černochová (Czech Dental Chamber, 2009)
Transplantation of teeth is a method of choice for substitution of missing teeth especially in growing patients. For the therapy of retained teeth tooth transplantation is indicated in cases, where a disadvantageous position of the impacted tooth does not make it possible to include it into the dental arch. The aim of the present paper is to describe a complex survey of available information on tooth transplantation. The historical development is described as well as indications and target groups for tooth transplantation. Factors influencing success are described in detail and the procedure of transplantation is outlined.